Prevalence of depression, anxiety, and stress among the general population during COVID-19 pandemic: A systematic review - Ibrahim M. Alqahtani; Abdulaziz M. Al-Garni; Majed S. Abumelha; Saleh A. Alsagti; Fatimah A. D. Alshehri; Abdulrahman A. Alqahtani; Saif S. S. Alkhidhran (Journal of Family Medicine and Primary Care)
The emergence of Coronavrus Disease 2019 (COVID-19) has resulted in significant impacts on individuals and the whole world. It can lead to severe health outcomes that may lead to death. It also affects the psychological status and mental health of the individuals due to fear of infection, isolation, and quarantine. To assess the prevalence of depression, anxiety, and stress among the general population during the COVID-19 pandemic by reviewing the previous studies and original articles published on this subject. Both PubMed and Google Scholar databases were searched for scientific articles that reported the prevalence of depression, anxiety, and/or stress among the general population during the COVID-19 pandemic. The included terms used for the search process were “Prevalence, Anxiety, Depression, Stress, COVID-19, Pandemic, Psychological impact.” The inclusion criteria were original articles written in the English language and conducted on the general population and reported the prevalence of depression, anxiety, and/or stress during COVID-19. A total of 2204 articles were obtained; only nine articles were eligible for the inclusion criteria. The included studies involved a total number of 19,277 participants and covered eight countries. The age range of participants was less than 18 years to 90 years, and female participants were more dominant compared to male participants in the majority of the studies. The prevalence of depression, anxiety, and stress was varied based on the region of studies and affected factors; however, the COVID-19 pandemic increased the prevalence of the three items.